Alcohol use and alcohol-related problems among adolescents in China: A large-scale cross-sectional study. Issue 38 (September 2016) - Guo, Lan; Deng, Jianxiong; He, Yuan; Deng, Xueqing; Huang, Jinghui; Huang, Guoliang; Gao, Xue; Zhang, Wei-Hong; Lu, Ciyong
Abstract : Abstract: Alcohol misuse among adolescents is a common issue worldwide and is an emerging problem in China. This study aimed to investigate the prevalence of alcohol drinking and alcohol-related problems among Chinese adolescents and to explore their risk factors and connections. A cross-sectional study using an anonymous questionnaire was conducted among junior and senior high school students between 2010 and 2012. Data on self-reported alcohol use, alcohol-related problems, school factors, family factors, and psychosocial factors were collected. Descriptive analyses were made of the proportions of sociodemographics, family, school, and psychosocial factors. Multilevel logistic regression models were conducted to analyze the risk factors for alcohol drinking and alcohol-related problems. Of the 105, 752 students who ranged in age from 9 to 21 years, the prevalence of current drinking among students was 7.3%, and 13.2% students reported having alcohol-related problems. Male students were 1.78 (95% confidence interval [CI] = 1.69–1.87) times more likely to be involved in current drinking and 1.86 (95% CI = 1.79–1.93) times more likely to have alcohol-related problems. Higher grade level students were at a higher risk of current drinking (adjusted odds ratio [AOR] = 1.09, 95% CI = 1.05–1.13) and having alcohol-related problems (AOR = 1.43, 95% CI = 1.42–1.58). Older students were more likely to report current drinking (AOR = 1.06, 95% CI = 1.04–1.17) and having alcohol-related problems (AOR = 1.83, 95% CI = 1.82–1.85). Having poor classmate relations (AOR = 1.28, 95% CI = 1.03–1.37), having poor relationships with teachers (AOR = 1.08, 95% CI = 1.00–1.16), and below average academic achievement (AOR = 1.50, 95% CI = 1.41–1.59) were positively associated with current drinking. Moreover, students with suicidal ideation were at a higher risk of current drinking (AOR = 1.70, 95% CI = 1.61–1.81) and having alcohol-related problems (AOR = 2.08, 95% CI = 1.98–2.16). Having higher Center for Epidemiology Scale for Depression scores was positively associated with current drinking (AOR = 1.09, 95% CI = 1.05–1.11) and having alcohol-related problems (AOR = 1.08, 95% CI = 1.06–1.18). Alcohol drinking and alcohol-related problems among Chinese adolescents are major public health problems, and effective preventive programs will require full consideration of the individual, social, and environmental factors that facilitate and prevent alcohol use.